Kebijakan Formulatif Pengaturan Perampasan Aset yang Berasal dari Tindak Pidana Korupsi - Hardian Prasetya; Teguh Suratman (Postgraduate University of Merdeka Malang, 2022)
This study aims to formulate policies for regulating asset forfeiture from corruption crimes in ius constitutum or positive law in Indonesia and formulate policies for regulating asset forfeiture from corruption crimes in ius constituendum or future law in Indonesia. The method used in this study is normative legal research method. The results show that the formulative policy of asset forfeiture in positive law in Indonesia is still regulated in general and broadly in the Criminal Code, Law No. 20 of 2001 jo. Law No. 31 of 1999 on the Eradication of Corruption and Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering. In addition, it is also regulated in PERJA Number: 013/A/JA/06/2014 concerning Asset Recovery, PERJA Number: PER-027/ A/JA/10/2014 concerning Guidelines for Asset Recovery and PERJA Number: 7 of 2020 concerning the Second Amendment to the Regulation of the Attorney General Number: Per-027/A/JA/10/ 2014 concerning Guidelines for Asset RecoveryDOI: https://doi.org/10.26905/mlj.v3i2.9215